UPAYA PENCEGAHAN TERBENTUKNYA INKLUSI SILIKAT FASA PADAT PADA PERMUKAAN BILET BAJA KARBON RENDAH - Dahar, Rosfian Arsyah (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
The mechanical properties ofsteel billets, slabs orblooms are controlled by the chemical compositionand by the treatment and/or mechanical treatment to which the steel is submitted. However, structuraldefects, such as non-metallic inclusions, are also responsible for theperformance ofthis material when it issubmitted to mechanical stress. The problem in clean steel manufacture is to reduce the overall numbers ofinclusions andtheir size distribution. By controlling the amount, distribution, size andchemical compositionofnon-metallic inclusions, it is possible to get clean steel with good quality. The identification ofthe natureand the control of inclusionformation inliquid steel are very importantfor steelcleans. The main purpose ofladlefurnacetreatment is to ensure that themolten steel has therequired temperature when theladle is takenover at downstream secondary metallurgy units or at a continuous caster. Besides the temperature of themelt, thesteel analysis is also calculated on-line, basedon the influences ofalloying element additions anddesulphurisation. Minimization of the number of solid silicate inclusions must take place after deoxidantaddition andbefore pouring into the CCM. A ladle furnace is used to relieve the primary melter of mostsecondary refining operations, and its primaryfunctions are